Analysis on the fatigue properties of vertical vibration compacted lime–fly ash-stabilized macadam. (30th November 2017) - Xue, Jinshun; Jiang, Yingjun
Highlights: Fatigue performances of the LFASM compacted by Vibration Testing Method are evaluated. Fatigue equations of LFASM are established. Suggested values of tensile strength structure coefficient of the LFASM are proposed. Abstract: Although lime–fly ash-stabilized macadam (LFASM) is a common material for the road base course of semi-rigid pavements, the fatigue performance of compacted LFASM has been rarely studied through the vibration testing method (VTM). In this work, LFASM was designed using the VTM instead of the quasi-static testing method. The vibration compaction test method was used to determine optimum water content and maximum dry density, and cast specimens were analyzed through the vibration pressure producing specimen method. The fatigue performances of the LFASM specimens were evaluated, and the fatigue equations of LFASM were then established. The suggested values for the coefficients of the tensile strength structure of LFASM were proposed on the basis of the derived fatigue equations. Results show that the splitting strength of LFASM increased with increasing lime and fly ash contents. However, the rates of the increase in the splitting strength of LFASM gradually declined. The splitting strength of LFASM with skeleton-dense (SD) gradation was higher than that of LFASM with gradation of specification (SG). The fatigue life of LFASM conformed to the two-parameter Weibull distribution, and the established fatigue equations accurately reflected the fatigue life of CRPMs. LFASM with SD gradation showed potentially better fatigue resistance than LFASM with SG. As the contents of lime and fly ash increased, the effect of gradation on the fatigue performance of LFASM became negligible. The failure probability based on the fatigue equations was 50%, the values of the regression coefficient a of the fatigue equations ranged from 1.198 to 1.278, and the values of coefficient b ranged from 0.051 to 0.059. The formula of the tensile strength structure coefficient K s was proposed. The coefficients for tensile strength structure were recommended after considering various factors. The value of K s obtained in this work can be used to effectively guide the design of pavement structures. The pavement designed with VTM offers many advantages in terms of crack resistance and durability.